Comparison between two epidural analgesia maintenance techniques at a regional hospital - Sehlapelo, Mathabe (My University, 2020)
Background Maintaining a labour epidural with programmed intermittent epidural bolus (PIEB) with patient controlled epidural analgesia (PCEA) using automated pumps has been shown to be beneficial compared to continuous epidural infusion (CEI) with intermittent epidural bolus (IEB). The aim of the study was to compare these two techniques for labour analgesia with regards to haemodynamics, drug consumption, motor blockade, mode of delivery and to describe patient satisfaction and adverse effects. Methods A prospective, contextual and comparative study was used. One hundred and twenty patients in the active phase of labour were recruited. Participants were randomly assigned to either the CEI with IEB (Group A, n = 60) or PIEB with PCEA (Group B, n = 60). The labour epidural was activated and maintained with bupivacaine 0.0625% and fentanyl 2 ug/ml. Achieving a bilateral T10 sensory level and a visual analogue score less than 30 mm was considered as Time Zero (T0), this timing was continued until delivery. Results There were no significant differences in participants’ characteristics between the groups. A higher percentage of satisfaction was recorded in Group B. Hypotension occurred significantly more often in Group A (p = 0.002). Group B had less drug consumption (p < 0.01), rescue boluses (p < 0.01) and motor blockade (p = 0.02). Group A had more assisted deliveries (p = 0.01). Adverse effects occurred similarly in both groups. Conclusion PIEB with PCEA for maintenance of labour epidural analgesia results in better participant satisfaction, more cardiovascular stability, less drug consumption and less motor blockade with more unassisted deliveries. Labour epidural analgesia techniques using algorithms are proving to be superior to other maintenance techniques. Although more costly, PIEB with PCEA appears to convey benefits.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology, to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020